Solution of Certain Systems of Dual Integral Equations with Bessel Kernels and its Application in the Theory of Elasticity - Gaszyński, J. (Engineering Transactions, 1976)
The paper deals with the construction of solutions for the systems of dual integral equations of the form [...] where the weight functions  have the following forms [...].The method of reducing the systems (1) to the system of differential-integral equations of the second kind and second order is presented. The results obtained are illustrated by the solution of the contact problem of coupled thermoelasticity with mixed boundary conditions under the assumption of thermal insulation of the boundary.